Effects of wire tension on the biomechanics of asymmetric four-ring circular external skeletal fixator constructs - Cross, A. R.; Lewis, D. D.; Rigaud, S.; Mackinzie, G. B.; Rapoff, A. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
This study evaluated the effects of fixation wire tension (0 kg, 30 kg, 60 kg, and 90 kg) on the biomechanics of a four ring asymmetric circular external fixator construct in four testing modes (axial compression, medio-lateral bending, craniocaudal bending, and torsional loading) using a gap fracture model. Wire tension had a significant direct effect on gap stiffness in all of the testing modes. Axial compression load-deformation curves exhibited non-linearity, characteristic of the self-tensioning effect observed with fine wire fixation. Bending loaddeformation curves had two discrete linear segments, attributable to slipping of the bone models on the fixation wires, once a critical bending moment was exceeded. Torsional loading caused a gradual ‘windup’ of the construct which was followed by a linear load-displacement curve. Increasing wire tension had a small but significant effect on gap stiffness, which generally diminished as higher tensions were applied, thus demonstrating the need for adequate initial construct design to achieve sufficient stability during fracture healing.
Keywords: llizarov; Circular External Skeletal Fixator; Biomechanics